A dying radio AGN in the ELAIS-N1 field. Issue Volume 15:Issue S356(2019) (October 2019) - Randriamanakoto, Zara
Abstract: We use low-frequency GMRT observations and 1.4 GHz VLA archival data to study the radio spectrum of a dying radio galaxy discovered in the field of ELAIS-N1. With a linear size of ˜ 100 kpc at a redshift z ˜ 0.33, the diffuse source J1615+5452 exhibits a steep spectral index and a convex radio spectrum. Its radio morphology also seems to lack compact features such as a nuclear core, relativistic jets and hotspots. We record a spectral curvature Δα ≍ -1 and a synchrotron age estimated between 34 - 70 Myr. These characteristics suggest that J1615+5452 is most likely a remnant radio AGN that has spent more than half of its total lifetime in the quiescence phase. The detection of such an elusive source is important since it represents the final phase in the evolution of a radio galaxy unless the nuclear core gets replenished with fresh particles and undergoes a restarting activity.